Public Hearing and Referendum as Political Legitimacy - Klongwijak, Thasana (Academic MCU Buriram Journal, 2023)
The purposes of this article were: 1) to study the concept of public hearing, 2) to study the concept of referendum, 3) to study the concept of political legitimacy, and 4) to analyze how they are related to each other. This study used cases of constitution drafting in 1997 and constitution drafting in 2007, 2017 for analysis base on four concepts. The study found that the concepts of public hearing, referendum and political legitimacy are related. That is to say, the concept of public hearing has strategies and tactics to support political legitimacy, while the concept of referendum is a form of direct democracy in which the people have the power to decide on major national issues by using the principle of majority rule. Political legitimacy in the case of public hearing arise from the fact that the Constituent Assembly has allowed both side of people who agree or disagree to express their opinions so widely. This made members of the parliament voted in favor with overwhelming votes although the constitution drafting in 1997 does not have a referendum. As for the draft constitution of the Kingdom of Thailand 2007 and 2017, despite political legitimacy due to being approved by more than half according to the principle of majority rule through a referendum. However, both constitutions were reversed, criticized by many parties for not allowing the people to participate in expressing their opinion widely. As the result, the constitution had problems with political legitimacy later on.